From energy security to security of energy eervices: The role of gendered innovations in living labs - Batinge, B.; Musango, J.K.; Ceschin, F.; Ambole, A.; Smit, S.; Mukama, M.; Petrulaityte, A. (South African Journal of Industrial Engineering, 2022)
Energy security remains a concern in Sub-Saharan Africa. The conceptualisation of energy security at the urban household level has shifted from the security of energy supply to the security of energy services, which is focused more on the demand side. Women and young girls are affected the most by insecure energy services. However, energy policy discourses often fail to focus on the security of energy services or to recognise gender roles in the provision of energy services at the household level. It is therefore imperative to develop innovative and gender-sensitive energy services solutions with a new paradigm of participatory solution design, such as living labs. We assessed living labs and the energy security landscape in poor urban environments through a systematic literature review, and proposed a framework for demonstrating how living labs could be used as a lever to promote the security of energy services. The security of energy services in poor urban households could be improved by harnessing the different innovative strengths of the respective genders. Living labs provide an ideal space for co-generating, co-designing, and co-learning to produce tailored energy services solutions. There is a need for a collaborative effort in resourcing researchers to undertake practical investigations of interactive multi-stakeholder platforms with those who are intended to benefit from the policy to increase its impact and to bridge the science-policy divide. © 2022, South African Institute of Industrial Engineering. All rights reserved.
Keywords: accès à l'électricité; afrique; afrique subsaharienne; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

La vulnérabilité face aux changements climatiques - Gagnon-Bouchard, Laurie (Spirale, 2022)
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; cours; environnement; fem3600; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; écoféminisme

Ville féministe : notes de terrain - Kern, Leslie (Les éditions du remue-ménage, 2022)
À qui appartient la ville? Sûrement pas aux femmes. Souvent le théâtre des violences ordinaires ou frontales, la ville repose sur des fondations sexistes. Kern s'attarde à la manière dont les relations de genre, de classe, de race, d'âge se déploient dans la ville. Elle nous invite à redéfinir et à nous réapproprier les espaces urbains. Comment rendre nos villes plus féministes? Partant de son expérience quotidienne de citadine à différentes époques de sa vie (enfant, adolescente, étudiante, travailleuse, militante et mère), elle s'appuie sur les théories d'urbanisme, des travaux de géographes féministes et des références à la culture pop pour montrer comment une ville genrée qui s'embourgeoise exclut les populations marginalisées, mais également pour évoquer les possibles configurations d'une ville plus inclusive.
Keywords: approches et analyses; cours; design; discipline; environnement; fem1250; inégalités; premier cycle; racisme; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; urbanisation; urbanisme; violences

Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite